2011
DOI: 10.1143/jjap.50.010102
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation on Longitudinal Optical Phonon Mode Decay and Heat Transport in a Silicon Nano-Structure Covered with Oxide Films

Abstract: A series of molecular dynamics (MD) simulations have been conducted to investigate the heat transport in terms of the phonon dynamics in nanoscale silicon (Si). This work is motivated by a concern over the stagnation of heat at the drain region of nanoscopic transistors, owing to this, a large amount of optical phonons with a low group velocity are emitted from hot electrons, which are ballistically transferred through channel region. The point of this work is the explicit inclusion of the SiO 2 film in the MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The bulk phonon Si dispersion relation shown in Fig. 3a agrees with that obtained by diagonalizing the dynamical matrix (11). In the bare SiNW, as shown in Fig.…”
Section: Resultssupporting
confidence: 80%
“…The bulk phonon Si dispersion relation shown in Fig. 3a agrees with that obtained by diagonalizing the dynamical matrix (11). In the bare SiNW, as shown in Fig.…”
Section: Resultssupporting
confidence: 80%
“…5,6,10 and 11. In our previous MD study, 21 it was found that the thermal energy diffusion process is retarded with thinning the Si core thickness and is less dependent on the outer SiO 2 film thickness. Therefore, it can be concluded that the increasing the surface-to-volume ratio of the inner SiNW by the oxidation is responsible for the thermal conductivity degradation.…”
Section: Resultsmentioning
confidence: 88%
“…In the practical NW, the SiO 2 film would modify the phonon energy dispersion, and thus phonon energy spectrum, group velocity and relaxation time, due to the oxide-induce strain and SiO 2 /Si interface roughness. 5,6,20,21 Therefore the insulating oxide film should be included in the simulation system.…”
mentioning
confidence: 99%